Effective development of the modern economy: problems and prospects - Baranova N. A., Kruglov V. N., Kulakova S. V., Kul'chikova Z. T., Lebedev V. E., Lilimberg S. I., Panina G. V., Vinogradova N. P., Lilimberg S. I., Selezniova T. O., Maer O. I., Malanina A. A., Mfliarenko O. I., Baikova E. I., Minakov A. V., Agapova T. N., Minitaeva A. M., Mishulina O. V., Gorelova N. S., Odinokova T. D., Sokheilinia K., Shpak A. S., Shcherbakova N. S., Tuzandekhdzhani M. (Effective development of the modern economy: problems and prospects, 2025)
the creation of a dynamically functioning innovation economy, maintaining its competitiveness in the conditions of geopolitical struggle, unprecedented sanctions pressure from the West are the priority tasks of modern Russia's development. One of the determining factors of an effectively operating innovation economy is the provision of highly sustainable development of regions, including such backbone structures as scientific and technological complexes. The author's interpretation of this aspect of the topic is proposed. The novelty in the continuation of its comprehension lies in the retrospective analysis of a long period, including the second half of XX – the first quarter of XXI centuries, and at the same time continuous in the context of the region's transition to an innovative type of development. The study of experience in creating a modern model of STC in the region is based on the theoretical and methodological units of the theory of regional development, and, above all, the concept of «points of growth» as its special section. It emphasizes the stimulation of «knowledge economy», development of innovation infrastructure, transfer of scientific achievements into production, maintenance of technological security, etc., as such points. The research methods traditional for retrospective regionalism as a branch of knowledge are used: interdisciplinary, periodization, retrospective and prospective analysis, problem-chronological. Traditional research methods for retrospective regionalism as a branch of knowledge are used: interdisciplinary, periodization, retrospective and prospective analysis, problem-chronological.
Keywords: регион; region; инновационное развитие; технологическая безопасность; technological security; innovative development; научно-технологический комплекс; трансфер достижений науки в производство; Уральский экономический регион; scientific and technological complex; transfers of science achievements into production; Urals Economic Region